RFID based Attendance Management System - Shashank Shukla; Shailee Shah; Pooja Save (Institute of Advanced Engineering and Science, 2013)
Radio-frequency identification (RFID) is a technology that uses radio waves to transfer data from an electronic tag, called RFID tag or label, attached to an object, through a reader for the purpose of identifying and tracking the object. RFID technology is a matured technology that has been widely deployed by various organizations as a part of their automation systems. In this project, an RFID based system has been built in order to produce an attendance management system. An automated attendance management software will not only make the entire process simple, but will also provide a well-structured and analyzed report of the pattern of student attendance and time management, which can further help in allocating and using the human resources in an organization to the maximum possible benefit. This system consists of two main parts which include: the hardware and the software. The hardware consists of a motor unit and RFID reader. The RFID reader, which is a low-frequency reader (125 kHz), is connected to the host computer via a serial to USB converter cable. The Time-Attendance System GUI is developed using Visual Basic.Net. The Attendance Management System provides the functionalities of the overall system such as displaying live ID tags transactions, registering ID, deleting ID, recording attendance and other minor functions. This interface was installed in the host computer.DOI:http://dx.doi.org/10.11591/ijece.v3i6.3961